EMPOWERMENT OF THE TEMBUKU DISTRICT VILLAGE TRADITIONAL MARKET IN BANGLI - Nengah Landra (Unmas Press, 2019)
In the era of globalization, the development of modern markets will threaten the existence of traditional markets. Therefore, efforts are needed to protect and empower traditional markets in order to remain in the midst of the turmoil of modernization. Not only empowering the physical market, but also empowering market traders. The revitalization has succeeded in changing the conditions of the Peninjoan Village in Tembuku in Bangli Regency both in terms of physical, management, and social aspects, as well as empowering market traders in it by implementing capacity building for market managers and traders by conducting training through counseling, giving authority for traders in determining the search for capital, and approve the formation of a market association if market traders want it. However, in part, the new physical revitalization program can be partially implemented because of the very limited allocation of funds from the Faculty of Economics, Denpasar.